Timişoara, de la petite Vienne du Banat à la Capitale européenne de la culture - Amandine Dargaud (EchoGéo)
Since the fall of the socialist regimes in Eastern Europe, the institutional will to redefine the postsocialist cities' image and identity involves the appreciation of pre-socialist heritage on one hand and the rejection of socialist memories and legacies on the other hand. Thus, in Timişoara (Romania), the municipality is implementing urban renewal and marketing policies of patrimonialization of the historic center and valorization of the Austro-Hungarian past. However, these policies deals with the weakness of institutional tools, criticisms of the dominant narrative of the city promoted by institutional actors and their relays – like the TM2021 association in charge of preparing the European Capital of Culture event in 2021 –, but also the permanence of dissonant and even conflicting legacies of socialism in the context of europeanization.